Enhanced photocatalytic oxidation technology - Sun, Darren Delai (2008)
The report discussed the enhanced photocatalytic oxidation technology that has advantages over the conventional water pretreatment process. This study also investigated the possibility to improve photocatalytic oxidation efficiency by coating titanium dioxide (TiO2) onto haematite particles for wastewater purification.